The Short-Run Economic Impact of Summer 2020 Protests in Addis Ababa : A Brief Look at the Evidence from a High-Frequency Phone Survey of Firms - Abebe, Girum; Bundervoet, Tom; Wieser, Christina (World Bank, Washington, DC, 2021)
It is long recognized that instability is inimical to economic growth. Instability produces uncertainty, amplifies risks, undercuts high-return investment, and diverts public policy towards short-term and quick-fix policies. Instability, accompanied by violent protest and riots, not only impacts current productive assets but also thwarts physical and human capital accumulation, weakening future growth. In the last two years, non-state conflict, civil unrest, and violent protest was rife in Ethiopia. While such conflicts are known to be barriers to a peaceful political and economic transition, little is known about how they have impacted the private sector. In this brief, we examine the economic impact of one specific event that led to the outburst of violent protests on firms in Ethiopia. This paper also shows that the internet shutdown affected a large share of SML firms than own-account firms. Not surprisingly perhaps, young and large firms are more likely to run businesses that depend on an online presence. Authors also see sector differences in the impact of internet shutdown on businesses. About 12 percent of firms in the industry sector and 6 percent of firms in the service sector report to have experienced disruptions to the business due to the internet shutdown. There is, however, little variation in the impact of internet shutdown on male, and female-owned firms.